2012
DOI: 10.1016/j.biomaterials.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intraluminal contact mediated guidance signals on axonal mismatch during peripheral nerve repair

Abstract: Publication InformationDaly, WT,Yao, L,Abu-rub, MT,O'Connell, C,Zeugolis, DI,Windebank, AJ,Pandit, AS (2012) b s t r a c tThe current microsurgical gold standard for repairing long gap nerve injuries is the autograft. Autograft provides a protective environment for repair and a natural internal architecture, which is essential for regeneration. Current clinically approved hollow nerve guidance conduits allow provision of this protective environment; however they fail to provide an essential internal architect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 40 publications
0
58
0
1
Order By: Relevance
“…More advanced therapies are also well documented where the conduit is used to deliver growth factors (e.g. neurotrophin-3/neurotrophin-4 [33]), cytoprotective agents [34], the inclusion of internal guidance structures (as channels [19,35] or fibres [31,36e38]) and where the conduit is used in combination with a cell therapy, including the local delivery of support cells for stimulating proximal axon regeneration (e.g. Schwann cells [39,40]) or adult-derived stem cells, both as bone marrow-derived mesenchymal [41] or adipose-derived cells [42e45]).…”
Section: Discussionmentioning
confidence: 99%
“…More advanced therapies are also well documented where the conduit is used to deliver growth factors (e.g. neurotrophin-3/neurotrophin-4 [33]), cytoprotective agents [34], the inclusion of internal guidance structures (as channels [19,35] or fibres [31,36e38]) and where the conduit is used in combination with a cell therapy, including the local delivery of support cells for stimulating proximal axon regeneration (e.g. Schwann cells [39,40]) or adult-derived stem cells, both as bone marrow-derived mesenchymal [41] or adipose-derived cells [42e45]).…”
Section: Discussionmentioning
confidence: 99%
“…Further in vitro analysis demonstrated that such materials, largely attributed to their surface features, not only facilitate bidirectional cell alignment, but also maintain tenogenic phenotype in vitro [360]. Further, preclinical experimentation in peripheral nerve repair and in tendon small and large animal models enhanced the clinical potential of these fibres, as judged by improved structural alignment and biomechanics [361][362][363]. Using an isoelectric focusing setup, aligned collagen fibres have been produced with ultrastructural characteristics and physical properties similar to native tendon [364,365].…”
Section: Bottom-up Approached For Tendon Repair Based On Natural In Omentioning
confidence: 99%
“…Among 165], collagen gel tubes [166], bioartificial nerve graft seeded with Schwann cells [167], Schwann cells modified to over-express specific growth factors [168][169][170], conduits of synthetic materials [147,153,171,172], the infusion of antibodies [173], gradients of factors within tubes [174], allographs [175], factors that induce inflammation [149,176], pseudo nerves [177], alginate gel [178], biodegradable polymer tubes [179], tubes filled with platelet-rich plasma [180][181][182], and arteries, veins and muscle tubes [160, 183,184]. None of these techniques induces more effective axon regeneration than autologous sensory nerve grafts [20,31,[185][186][187][188]. Therefore, despite their significant limitation in inducing axon regeneration, sensory nerve grafts remain the "gold standard" for clinical peripheral nerve repair [3,99,110,106,148,[189][190][191][192][193].…”
Section: Alternative Tested Techniques For Bridging Nerve Gapsmentioning
confidence: 99%